Review of cobalt toxicokinetics following oral dosing: Implications for health risk assessments and metal-on-metal hip implant patients. (May 2015) - Tvermoes, Brooke E.; Paustenbach, Dennis J.; Kerger, Brent D.; Finley, Brent L.; Unice, Kenneth M.
Abstract Cobalt (Co) can stimulate erythropoietin production in individuals at doses exceeding 25 mg CoCl2/day. Co has also been shown to exert effects on the thyroid gland, heart and nervous system at sufficient doses. The biological activity of Co is dictated by the concentration of free (unbound) ionic Co2+. Blood concentrations, as well as, urinary excretion rates of Co are reliable biomarkers for systemic Co exposure. A recent series of human volunteer Co-supplement studies simultaneously measured Co blood and urine concentrations, as well as, Co speciation in serum, and a number of biochemical and clinical parameters. It was found in these studies that peak Co whole blood concentration as high as 117 μg/L were not associated with changes in hematological parameters such as increased red blood cell (RBC) count, hemoglobin (Hgb) or hematocrit (Hct) levels, nor with changes in cardiac, neurological or, thyroid function. Using a Co biokinetic model, the estimated Co systemic tissue concentrations (e.g., liver, kidney, and heart) following 90-days of Co-dietary supplementation with ∼1 mg Co/day were found to be similar to estimated tissue concentrations in implant patients after 10 years of exposure at continuous steady state Co blood concentration of ∼10 μg/L. This study is the first to present modeled Co tissue concentrations at various doses following sub-chronic and chronic exposure. The modeled steady state tissue Co concentrations in combination with the data on adverse health effects in humans should help in the characterization of potential hazards associated with increased blood Co concentrations due to exposure to dietary supplements or cobalt-chromium (Co-Cr) containing implants.